Improving an Ovulation Rate in Women with Polycystic Ovary Syndrome by Using Silymarin - Mohammed A.Taher; Yaser A.Atia; Manal K.Amin (College of Pharmacy University of Baghdad, 2017)
Polycystic ovary syndrome(PCOS) is a heterogeneous disorder of uncertain etiology , it is the most common endocrinopathy in women and most common cause of anovulatery infertility ,characterized by chronic anovulation and hyperandrogenemia .The present study was designed to investigate the effect of silymarin which is known to have antioxidant and insulin sensitivity effects on the  levels of glucose, insulin ,testosterone ,leutinizing hormone(LH) and progesterone .Ovulation rate and Homeostasis Model Assessment of insulin Resistance (HOMA) ratio were determined .A 3-months of treatment were conducted in 60 PCOS patients in three well-matched groups .The first one (n=20),received silymarin(750mg/day)  .The second group received metformin(1500mg/day) while the third group treated by combination of metformin (1500mg/day )and silymarin (750mg/day). All these groups  had taken the drugs in divided doses. The results showed significant improvement in all parameters at the end of treatment .The percentage of increment in progesterone levels after completion of treatment were 12.12, 15.9, and 17.51 in groups 1, 2, and 3 respectively and the number of patients  ovulated after 3 months of treatment  were 4,5, and 10 in groups 1,2, and 3 respectively. However they are more better in group of patients who were treated with combination of silymarin  with metformin.In conclusion the addition of silymarin to metformin in treatment of PCOS patients has improving effect on disturbed hormones and ovulation rate. Key words: Polycystic ovary syndrome, silymarin, ovulation rate,metformin